2011
DOI: 10.1038/nature10395
|View full text |Cite
|
Sign up to set email alerts
|

The thermodynamic meaning of negative entropy

Abstract: To clarify the implications of our result, we note that, although the erasure processes we considered in our Letter can have negative work cost (that is, they can yield work), they do not violate the second law of thermodynamics, because they are not cyclic processes. A negative work cost is associated with the consumption of entanglement, which can only be restored by doing work. Our results are also consistent with the original unconditional form of Landauer's principle, which says that if there is no inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(103 citation statements)
references
References 3 publications
3
100
0
Order By: Relevance
“…This result provide a thermodynamic operational meaning for negative conditional entropy, extending earlier studies in which this negativity had found information-theoretical interpretations only. [22,23] Additionally, it has been noted [22] that the above result also indicates that quantum discord can properly quantify the difference between the work costs of erasure by using quantum or, alternatively, classical memories Q.…”
Section: Wðajqþ5sðajqþ K B Tln ð2þmentioning
confidence: 72%
See 4 more Smart Citations
“…This result provide a thermodynamic operational meaning for negative conditional entropy, extending earlier studies in which this negativity had found information-theoretical interpretations only. [22,23] Additionally, it has been noted [22] that the above result also indicates that quantum discord can properly quantify the difference between the work costs of erasure by using quantum or, alternatively, classical memories Q.…”
Section: Wðajqþ5sðajqþ K B Tln ð2þmentioning
confidence: 72%
“…In the preceding derivations of quantumness of correlations, the concept of conditional entropy (or conditional information) plays a considerable role. Very recently, del Rio et al [22] showed that the standard formulation and implications of Landauers principle [40,41] are no longer valid in the presence of quantum information. Their result is that the work cost of erasure of information is determined by the entropy of the system, conditioned on the quantum information an observer has about it: the more an observer knows about the system carrying the information, the less it costs to erase the information.…”
Section: The Theoretical Model By Schulman and Gaveaumentioning
confidence: 99%
See 3 more Smart Citations